Frontline nursing leadership and safety culture in psychiatric care: Evidence from Aceh Mental Health Hospital - Putra, Ardia; Kamil, Hajjul; Yuswardi, Yuswardi; Darmawati, Darmawati (Acta Biomedica Atenei Parmensis, 2025)
Background and aim of the work: A safety culture enhances staff awareness, encourages reporting, and promotes improvement. First-line nursing managers greatly influence protocol adherence, communication, and error reporting. Improving their leadership is essential for increasing reporting and strengthening safety culture in inpatient settings. This study aims to evaluate the effectiveness of first-line nursing managers in fostering this culture at Aceh Mental Health Hospital. Material and methods: This research employs a quantitative, quasi-experimental design featuring a nonrandom pretest-posttest approach without a control group. The sample comprises 179 first-line managers from the Inpatient Ward of Aceh Mental Health Hospital, selected through a total sampling technique. Data collection unfolds across three stages: 1) Survey 1 conducted from August 5 to August 10, 2024; 2) a training session on enhancing the first-line nursing managers’ role in fostering patient safety culture from August 27 to August 29, 2024, and 3) Survey 2 from September 23 to October 5, 2024. The Hospital Survey on Patient Safety Culture version 2.0 and pre-and post-test questions are utilized for data analysis, employing descriptive and inferential statistical tests, including parametric statistics and paired t-tests. Results: The research findings illustrate significant discrepancies in how first-line nursing managers perceive their roles concerning patient safety culture (p-value = 0.004). Moreover, notable variations exist in the effectiveness of these managers across various dimensions, including team cooperation, staff management, organizational learning, response to error, supervisory support, communicating about errors, communication openness, incident reporting, management support, and patient handover processes within the Mental Health Hospital of Aceh (all p-values < 0.005). Conclusions: The Aceh Mental Health Hospital has seen improvements in patient safety culture due to optimized first-line managers’ roles. These leaders must understand management principles to reduce safety incidents. This culture encourages proactive incident reporting by nurses, fostering future patient safety initiatives. (www.actabiomedica.it).